Brand image and product quality effects on customer loyalty mediated by customer satisfaction - Muis, Indra; Sumardiono, Sumardiono; Manurung, Handrean; Melia, Melia (Gema Wiralodra, 2023)
This qualitative research explores the interplay between brand image, product quality, customer satisfaction, and customer loyalty in the context of Bekasi batik products. The study posits that customer satisfaction is a mediating variable between customer loyalty and the independent variables of brand image and quality. Using a simple random sampling technique, data was gathered through questionnaires distributed to 100 customers at a Bekasi Batik shop located within the Bekasi City Government Office Complex, representing a population of 456 people. Data collection occurred in August 2023 at the government office complex in Bekasi city, West Java, Indonesia. The findings highlight the pivotal role of brand image, product quality, customer satisfaction, and loyalty. The research suggests that business owners in the Bekasi Batik industry should reinforce the brand image by fostering trust, incorporating added values, and cultivating prestige. Additionally, enhancing product quality through improvements in appearance, reliability, durability, and overall product attraction is recommended. The study concludes that strengthening the brand image and improving product quality is essential for fostering customer satisfaction and loyalty. These implications underscore the importance of strategic measures for Batik Bekasi businesses to thrive in a competitive market by ensuring customer contentment and building enduring loyalty.